Perianal irritative dermatitis due to encopresis. - Schianchi, S.; Calista, D.; Arcangeli, F. (European Journal of Pediatric Dermatology, 2007)
Encopresis is characterized by chronic constipation with consequent formation of bulky fecal masses. The latter are responsible for obstruction of the fecal transit and constant drainage of liquid or semiliquid feces, giving rise sometimes to irritative contact dermatitis of the pseudomucosae and perianal skin. An actually 2-year-old girl is reported, presenting from the age of one a chronic perianal dermatitis particularly resistant to the commonest topical treatments.